2021
DOI: 10.1002/ijc.33817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of era of diagnosis on cause‐specific late mortality among 77 423 five‐year European survivors of childhood and adolescent cancer: The PanCareSurFup consortium

Abstract: Late mortality of European 5-year survivors of childhood or adolescent cancer has dropped over the last 60 years, but excess mortality persists. There is little information concerning secular trends in cause-specific mortality among older European survivors.PanCareSurFup pooled data from 12 cancer registries and clinics in 11 European countries from 77 423 five-year survivors of cancer diagnosed before age 21 between 1940 and 2008 followed for an average age of 21 years and a total of 1.27 million personyears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Moreover, Trabert et al 32 reported that in the SEER between 1988 and 2007, there was a change in the classification of mixed GCTs, with a decline of some types of histology and the final suggestion of cautious interpretation of some data. The rules for coding underlying causes of death can also give rise to too many deaths being attributed to the first primary neoplasm 1 and to deaths due to other causes being underestimated. The median followup of the cohort is 14 years beyond the fifth year after diagnosis and thus, new mortality and morbidity patterns could emerge with greater follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Trabert et al 32 reported that in the SEER between 1988 and 2007, there was a change in the classification of mixed GCTs, with a decline of some types of histology and the final suggestion of cautious interpretation of some data. The rules for coding underlying causes of death can also give rise to too many deaths being attributed to the first primary neoplasm 1 and to deaths due to other causes being underestimated. The median followup of the cohort is 14 years beyond the fifth year after diagnosis and thus, new mortality and morbidity patterns could emerge with greater follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Greater success in the treatment of children and adolescents with cancer and more expertise in supportive care have contributed to improving 5‐year survival for most cancers. Improving 5‐year survival has shown, however, that long‐term survivors remain persistently at greater risk of severe late effects, including excess late mortality, whatever the type of primary tumor 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolving treatment options and reductions in treatment intensity over time have resulted in significant reductions in the cumulative incidence of late mortality (both all-cause and cause-specific mortality) at various follow-up intervals among survivors treated in past decades. 2,3 Using cumulative incidence to examine trends in late mortality can identify differences between subgroups of survivors but cannot contextualize more broadly whether the mortality experienced among survivors varies significantly from what is expected in the general population. Relative and excess mortality are additional metrics that can be used to measure progress in cancer treatment and reduction in long-term adverse health effects among survivors.…”
Section: Introductionmentioning
confidence: 99%
“…The radiotherapy and chemotherapy regimens responsible for improving the survival rates for children and adolescents with cancer are not devoid of carcinogenic effects, and second malignancies are an important cause of death in long-term survivors. 11,12 The incidence of SMN is known to increase after radiotherapy, and the related risk persists for decades, long after the first tumor was diagnosed. 13 Many reports have been published, especially on Hodgkin lymphoma 14 and pediatric and adolescent cancer survivors, on the risk factors, the radiotherapy fields and doses, the type and dosage of chemotherapy, and the timing and type of follow up adopted in such patients.…”
Section: Introductionmentioning
confidence: 99%